Is Searching for Meaning in Life Related to Civic Engagement?: Individual- and Society-Level Moderators - Lin, Li (Frontiers in Psychology, 2019)
Going beyond previous research suggesting that the search for meaning in life (hereafter “search for meaning”) is associated with civic engagement, this study investigated the moderating effects of personal and cultural values on the associations between the search for meaning and two kinds of civic engagement (i.e., pro-environmental engagement and political engagement). Based on the dataset of the sixth wave of the World Values Survey (WVS), multi-level analyses showed that the association between the search for meaning (in terms of thinking about meaning and purpose of life) and pro-environmental engagement was stronger when people held stronger values of openness to change (vs. conservation) and prioritized environmental wellness. The association between the search for meaning and political engagement was stronger when people endorsed stronger values of openness to change, showed a greater interest in politics and attributed greater importance to politics. At the society level, the association between the search for meaning and civic engagement was stronger in societies with a lower power distance. Implications for individual differences of the meaning search are discussed.